The Phenomenon of Borrowing Foreign Words in Kurdish Novels; Deravé Teng, Waré Rondika and Mirové Beleç as Samples - Ibrahim Ahmed, Dildar; Ali Ahmed, Ara; Hessen Muhammed, Hamdiah (Journal of Duhok University, 2019)
This borrowing will affect all literary kinds of these people and the novel as one type of these literary works is submitting to this borrowing phenomenon which will be reflected in it. The reason is that the novelist may know more than one language, in addition to the effect of the environment, the religion and the neighborhood of these languages or these people, whether this effect is intentional or spontaneous. And in the three novels selected as a sample for research It showed that many foreign words have been borrowed by the novelist which eventually led to borrowing phenomenon of the foreign words.